Real-time monitoring of recombinant GFP expression in single-cell Komagataella phaffii through filamentous pelletization technology - Zheng Xiao; Cong Wenjie; Zhou Hualan; Zhang Jianguo (Reviews in Analytical Chemistry, 2023)
Komagataella phaffii is an important cell factory for recombinant protein production under methanol induction. Tracking of recombinant protein expression by single K. phaffii cell is a hot topic to identify the variation of expression level in submerge cultivation system. In this study, a platform system harnessing Aspergillus niger pellets for K. phaffii cell immobilization in fabricated glass plate was developed to measure the green fluorescent protein (GFP) expression of single cell using fluorescence microscope. This system was optimized through pellets preparation, K. phaffii cell absorption, inducer comparison, methanol concentration, flow velocity of medium, and obtaining a successful platform to track GFP expression of single K. phaffii cell. This system provided an on-line analytical technology to discover the heterogeneous capability of various K. phaffii cells.